Pemanfaatan E-Book Pembelajaran Sepak Takraw pada Mahasiswa - Aryanti, Silvi; Ramadhan, Arizky; Novritika, Novritika; Fitriana, Fitriana; Azhar, Samsul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the results of using the Flip PDF Professional e-book for sepak takraw learning among students (large scale trial). This research uses Research and Development by adopting Borg & Gall. In the previous research stage, a needs analysis, small-scale trials were carried out, and in this research, a large-scale trial was carried out on the use of the E-Book Flip PDF Professional Sepak Takraw Learning. The research subjects in the large-scale trial were 30 students in the third semester of the physical education, health and recreation study program at the Faculty of Teacher Training and Education, Sriwijaya University. The results of this research were 84.2% in the Feasible category. Conclusion, is that the sepak takraw e-book is suitable for use for student learning. Keywords: Utilization, E-Book, Large Scale